An impact of Lutheran theology on the formation of the church and society in Tanzania. Issue 2 (3rd June 2019) - Mahali, Faustin Leonard
Abstract: This article analyzes the impact of Lutheran theology on the life of the church and society in Tanzania, beginning with an introduction to the basic teachings of the Lutheran Church in Tanzania and their connection to the theological foundations of Reformation. The second part of the article deals with the story of the establishment of the Lutheran Church in Tanzania and how it interacted with the social context of Tanzania. Finally, the article correlates the basic theological foundations of Lutheranism and their influence on the formation of the church itself and society as a whole.